Creating outstanding classrooms : a whole-school approach - Knight, Oliver; Benson, David (New York : Routledge, Taylor & Francis Group, 2013)
'This timely new book outlines a whole-school approach to embedding a sustainable model of teaching and learning that puts the learner at the heart of the system. It provides an entire framework for ensuring all students achieve above their expectations; incorporating school vision, teacher professional development, assessment models, school culture, leadership and management, and core classroom practices. It takes what the current research suggests does - and does not - work and builds it into a practical approach that has been tried, tested and proven to work. Each section incorporates the research, a model of how this can be embedded across a school and then a training section that allows senior leaders in schools to teach the skill-set to others to ensure it can be embedded and reviewed. Covering all aspect of teaching and learning including curriculum design, teacher practices, assessment and leadership, the book features: - a clear planning framework that is easy to implement; - subject based case studies to exemplify good practice; - diagrams to clarify and consolidate information; - training activities throughout each chapter, also available to download at www.routledge.com/9780415831178. Designed to be used as a training tool for both new and established teachers, this book is essential reading for senior leaders that want to equip their teachers with the skills and knowledge to create a school of outstanding classrooms'--
Includes bibliographical references (pages 401-402) and index.
Keywords: School improvement programs; Student-centered learning; Effective teaching